Morphometric and flow cytometric evaluations of a putative natural hybrid of Centaurium (Gentianaceae) from Turkey - Çiçek, Mehmet; Yaprak, Ahmet Emre; Alan Ali̇ Ramazan (Phytotaxa, 2015)
A putative natural hybrid of Centaurium was discovered in a population composed of C. serpentinicola and C. tenuiflorum subsp. tenuiflorum in the vicinity of Köyceğiz (Muğla province, SW Turkey). Morphometric analysis performed using 14 diagnostic characters supported that the putative natural hybrid as an interspecific hybrid between C. serpentinicola and C. tenuiflorum subsp. tenuiflorum. Flow cytometric measurements revealed that C. serpentinicola and C. tenuiflorum subsp. tenuiflorum have similar nuclear DNA amounts (2.61 and 2.53 pg DNA/2C), whereas the putative hybrid have a significantly higher nuclear DNA amount (2.77 pg DNA/2C), and they have the same ploidy level.